Transformative Masculinity within Interreligious Organizations: Case Studies from Bali and Sidoarjo, Indonesia - Rohmawati, Wiwin Siti Aminah; Rahmatika, Arina; Gayatri, Erin; Sitek, Jessica (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2024)
Women's involvement in the Forum of Religious Harmony (Forum Kerukunan Umat Beragama - FKUB) is still rare. However, some FKUBs exhibit openness to women’s engagement. This study examines whether women’s involvement in the FKUB challenges the dominant beliefs and behaviors within religious groups and whether their involvement creates possibilities for change and contestation. Using a case study on the FKUB Bali and Sidoarjo and leveraging the theory from gender and masculinity studies to help frame the analysis, the study revealed two strategies used to involve women, which included forming a separate entity exclusively for women and developing an expanded familial framework inside FKUB. The findings also show that women's involvement is encouraged without altering the current structures. However, this study also discovered that the transformative masculinity exhibited by certain chairpersons contributed to the implementation of these strategies. They were strongly dedicated to gender equality, advocated for women's empowerment and involvement, and prioritized sustainable dispute resolution development. This study highlights the potential to expand research to include more cases, providing deeper insight into inclusion strategies and the role of transformative masculinity in progress toward gender equality._______________The original draft of this article has been presented at the 23rd Annual International Conference on Islamic Studies (AICIS), February 1-4, 2024, at Universitas Islam Negeri Walisongo Semarang, Indonesia.